Triatoma rosai sp. Nov. (hemiptera, triatominae): A new species of argentinian chagas disease vector described based on integrative taxonomy - Alevi, Kaio Cesar Chaboli [UNESP]; de Oliveira, Jader [UNESP]; Garcia, Ariane Cristina Caris [UNESP]; Cristal, Daniel Cesaretto [UNESP]; Delgado, Luiza Maria Grzyb [UNESP]; Bittinelli, Isadora de Freitas [UNESP]; Dos Reis, Yago Visinho [UNESP]; Ravazi, Amanda [UNESP]; de Oliveira, Ana Beatriz Bortolozo [UNESP]; Galvão, Cleber; de Azeredo-Oliveira, Maria Tercília Vilela [UNESP]; Madeira, Fernanda Fernandez [UNESP] (MDPI, 2020)
Chagas disease is the most prevalent neglected tropical disease in the Americas and makes an important contribution to morbidity and mortality rates in countries where it is endemic since 30 to 40% of patients develop cardiac diseases, gastrointestinal disorders, or both. In this paper, a new species of the genus Triatoma is described based on specimens collected in the Department San Miguel, Province of Corrientes, Argentina. Triatoma rosai sp. nov. is closely related to T. sordida (Stål, 1859), and was characterized based on integrative taxonomy using morphological, morphometric, molecular data, and experimental crosses. These analyses, combined with data from the literature (cytogenetics, electrophoresis pattern, molecular analyses, cuticular hydrocarbons pattern, geometric morphometry, cycle, and average time of life as well as geographic distribution) confirm the specific status of T. rosai sp. nov. Natural Trypanosoma cruzi infection, coupled with its presence mostly in peridomestic habitats, indicates that this species can be considered as an important Chagas disease vector from Argentina.
Keywords: Chagas disease; Experimental crosses; Molecular; Morphology; Morphometry; Triatomines